LOW-FAT COOKIES WITH CHLORELLA VULGARIS: EFFECTS ON DOUGH RHEOLOGY, PHYSICAL, TEXTURAL AND SENSORY PROPERTIES OF COOKIES - Dundar, Ayse Neslihan; Şahin-Cebeci, Oya Irmak; Saricaoglu, Furkan Turker (My University, 2023)
Microalgae are an enormous biomass used for fortification in foods that represent a promising source of protein. Enrichment of baked foods with microalgae is a challenge for its textural and structural impacts. In this study, dough rheology, physical, textural and sensorial properties of low-fat cookies with Chlorella vulgaris at various concentration (0.5, 1.5 and 3.0 %) were evaluated. Dry matter (93.20 to 94.89, %), protein (5.55 to 7.08, %), ash (0.47 to 0.55, %) and fat (12.35 to 13.37, %) contents of cookies were significantly increased with increasing microalgae concentration, whereas carbohydrate amount did not change significantly. The creep parameters, recovery behavior and viscoelasticity were increased with the addition of Chlorella biomass where results clearly showed more stiff dough structure. As the microalgae concentration increased, a significant color change (33.25, ?E) with high hardness (198.69 up to 330.86, N) and fracturability (88.66 up to 165.18, N) properties were observed.
Keywords: Chlorella vulgaris; Microalgae; Rheology; Low-fat cookie; Textural properties